Leading to excel : principles of transformation - Morrow, Richard, 1956- (Productivity Press, 2025)
Transformation, by definition, is a radical change in outcome - not incremental small movements. Too often organizations claim to have a transformation organization, yet little to no evidence of achieving anything close to the level of significant change from their prior state, let alone compared to its own industry's performance. What are the principles that exist in every transformation? This book details those principles found across industries including highly competitive automotive global competitors to local healthcare large and small. Leading radical improvement demands leadership "muscle, mentality, and motivation." It demands practice, repetition, and building muscles to "lift" organizations often facing heavy resistance. Those who excel in transformative change achieve a mental state envisioning the future, blocking out disruptions, and help others see the same view of a largely different future. In this book, the author coaches leaders on how to build the muscle, mental state, and motivate oneself and the organization to achieve radical change and focuses on radical improvement against industry competitors. Detailed examples in healthcare, manufacturing, aviation, automotive, and financial services are included to help those who struggle to achieve changes. The author shares his experiences in each of these industries as leaders learned and applied the principles of leading transformations. The author shares screen navigation in Minitab on how to measure, do measurement system analyses, and create in real time. Examples of dashboards and visual management techniques are also included.
Keywords: Leadership.; Organizational change.; elektronické knihy; electronic books